Scambaiting on the Spectrum of Digilantism. Issue 3 (2nd September 2019) - Sorell, Tom
Abstract : Digilantism is punishment through online exposure of supposed wrongdoing. Paedophile hunting is one example, and the practice is open to many of the classical objections to vigilantism. But it lies on a spectrum that contains many other kinds of digilantism. Scambaiting is among the other kinds. It consists of attracting online approaches from perpetrators of different kinds of online advance-fee fraud. Characteristically, it takes the form of protracted email exchanges between scammers and scambaiters. These exchanges are mainly down-to-earth and occasionally testy conversations about the details of fictitious money transfers or involved explanations of delays in payment. They succeed in their purpose if they waste a lot of their targets' time, but they can also be pursued as a sort of comic art form. Scambaiting exchanges seem often, but not always, to be relatively harmless. They therefore help to make intelligible a region of morally permissible digilantism on the spectrum of digilantism. Not that scambaiters never go too far, but their typical weapons inflict and risk inflicting far less harm than those of other digilantes, and there are actual scambaiting norms that have been chosen because of their relative harmlessness.